PERENCANAAN PLTS OFF-GRID MENGGUNAKAN HOMER PADA GEDUNG OPERASIONAL BTP KELAS II PADANG - Sepannur Bandri; Zuriman Anthony; Taufal Hidayat (Ensiklopedia of Journal, 2026)
The growing demand for electrical power and the heavy reliance on fossil energy resources encourage the use of sustainable renewable energy, especially solar energy. Padang Pariaman Regency has considerable potential for solar power development, indicated by an average solar irradiation of 4.62 kWh/m²/day, so the implementation of an off-grid Solar Power Plant (PLTS) system is the right solution to support energy independence and reduce carbon emissions. The objective of this study is to analyze the planning of an off-grid photovoltaic (PV) system at the Operational Building of Balai Teknik Perkeretaapian (BTP) Kelas II Padang from technical and economic aspects and evaluate its investment feasibility. The research method includes collecting primary data in the form of building electrical load profiles and site observations, as well as secondary data in the form of solar radiation data, component specifications, electricity consumption data, interest rates, and inflation rates. Technical and economic analyses are conducted through manual calculations to determine the capacity of solar panels, batteries, and inverters, as well as economic analyses in the form of Net Present Cost (NPC) and Cost of Energy (COE) calculations, which are then validated using HOMER software simulations. The analysis results show that both methods produce relatively comparable system configurations. Technically, the off-grid solar power system is designed with a solar panel capacity of 39,4 kW based on manual calculations and 45,2 kW based on HOMER software simulations, both of which are capable of meeting daily energy needs of 169,5 kWh with the support of a battery capacity of ±340 kWh that provides autonomy time of up to 48 hours and an inverter capacity of 80 kW which is above the peak load of 52,245.50 W. From an economic aspect, manual calculations produce a Net Present Cost (NPC) value of IDR 1,606,156,628 with a Cost of Energy (COE) of IDR 1,327/kWh, while the HOMER simulation produces an NPC of IDR 1,624,727,000 with a COE of IDR 1,405/kWh. Both methods show a positive NPV value, a Profitability Index greater than one, and a Discounted Payback Period below the project life, so that the off-grid solar power system can operate optimally is declared technically and economically feasible.Keyword: technical and economic analysis, solar energy, HOMER, Investment feasibility, off-grid solar photovoltaic system